Temporal and spatial variation in the soil seed bank of Nassella trichotoma (serrated tussock) in its native range - Garcia, Andrés (2021)
Serrated tussock (Nassella trichotoma (Nees) Hack. ex Arechav) is an unpalatable grass species that has been expanding in its native range and invading non-native ranges. In this study in its natural environment, we aimed to describe the spatial relationship between seed density, the cover and density of standing individuals of serrated tussock, the seasonal variation in the seed density in the soil seed bank, and to compare these results with those reported in non-native ranges. We took soil samples seasonally and recorded the cover and density of standing individuals of serrated tussock at two sites in the native Pampas grasslands in central-east Argentina. Seed density was evaluated by seedling emergence and seed extraction. Seed density showed a seasonality trend, with maximum values in the end of summer and minimum values in winter and spring. Seed density was independent of the cover and density of standing individuals of serrated tussock. The values of seed density were lower than those reported in the invaded ranges. Since seeds of serrated tussock are present in the seed bank regardless of the cover and density of its standing individuals, the maintenance of a high cover of desirable species may play a key role in preventing the establishment of serrated tussock in both its natural and invaded ranges.